Evolution of the mammalian dentate gyrus. Issue 3 (29th July 2015) - Hevner, Robert F.
ABSTRACT: The dentate gyrus (DG), a part of the hippocampal formation, has important functions in learning, memory, and adult neurogenesis. Compared with homologous areas in sauropsids (birds and reptiles), the mammalian DG is larger and exhibits qualitatively different phenotypes: 1) folded (C‐ or V‐shaped) granule neuron layer, concave toward the hilus and delimited by a hippocampal fissure; 2) nonperiventricular adult neurogenesis; and 3) prolonged ontogeny, involving extensive abventricular (basal) migration and proliferation of neural stem and progenitor cells (NSPCs). Although gaps remain, available data indicate that these DG traits are present in all orders of mammals, including monotremes and marsupials. The exception is Cetacea (whales, dolphins, and porpoises), in which DG size, convolution, and adult neurogenesis have undergone evolutionary regression. Parsimony suggests that increased growth and convolution of the DG arose in stem mammals concurrently with nonperiventricular adult hippocampal neurogenesis and basal migration of NSPCs during development. These traits could all result from an evolutionary change that enhanced radial migration of NSPCs out of the periventricular zones, possibly by epithelial–mesenchymal transition, to colonize and maintain nonperiventricular proliferative niches. In turn, increased NSPC migration and clonal expansion might be a consequence of growth in the cortical hem (medial patterning center), which produces morphogens such as Wnt3a, generates Cajal‐Retzius neurons, and is regulated by Lhx2. Finally, correlations between DG convolution and neocortical gyrification (or capacity for gyrification) suggest that enhanced abventricular migration and proliferation of NSPCs played a transformative role in growth and folding of neocortex as well as archicortex. J. Comp. Neurol. 524:578–594, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Comparative analysis of amniotes shows that the mammalian dentate gyrus is distinguished by convolution and nonperiventricular adult neurogenesis. Both features arose in stem mammals by enhanced migration of intermediate progenitors and radial glial progenitors in the embryonic dentate migration stream.